PENGARUH LINGKUNGAN SOSIAL, EKSPEKTASI PENDAPATAN DAN EFIKASI DIRI TERHADAP KEPUTUSAN BERWIRAUSAHA BUDIDAYA TANAMAN HIAS (Studi Kasus di Desa Pujoasri II Kecamatan Trimurjo Kabupaten Lampung Tengah) - Saras Febriyani; Yulita Zanaria; Angga Kurniawan (Universitas Muhammadiyah Metro, 2021)
The purpose of this study was to determine the effect of social environmental characteristics, income expectations, and self-efficacy on entrepreneurial decisions for ornamental plant cultivation in Pujoasri II village, Trimurjo sub-district, Central Lampung district. This type of research is a quantitative study with a research population of 50 people who cultivate ornamental plants, and only 33 samples were used. The results of this study indicate that there is an influence of the characteristics of the social environment on the entrepreneurial decision to cultivate ornamental plants and there is no influence of the characteristics of income expectations on the decision to entrepreneurship in the cultivation of ornamental plants. there is an influence of self-efficacy characteristics on the decision to entrepreneurship in ornamental plant cultivation and there is an influence on the characteristics of the social environment, income expectations and self-efficacy simultaneously on the decision to entrepreneurship in ornamental plant cultivation.